1985
DOI: 10.1111/j.1471-4159.1985.tb05514.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron Chelators on Dopamine D2 Receptors

Abstract: Nutritional iron deficiency induced in rats causes a selective reduction of [3H]spiperone binding in caudate nucleus. This effect can be reversed by iron supplementation in vivo. The possibility that iron may be involved in the dopamine D2 receptor was investigated by examining the effect of various iron and noniron chelators on the binding of [3H]spiperone in rat caudate nucleus. Iron chelators 1,10-phenanthroline, 2,4,6-tripyridyl-s-triazine, alpha, alpha'-dipyridyl, and desferrioxamine mesylate inhibited th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(31 citation statements)
references
References 29 publications
1
29
1
Order By: Relevance
“…RLS appears to be related to alterations in dopaminergic and opioid neuronal pathways within the central nervous system. This implies that iron deficiency plays a role in the etiology of RLS, since iron is a co-factor for dopamine production within nigrostriatal regions of the basal ganglia (i.e., substantia nigra, putamen, and caudate) and is a modulator of dopamine receptors [30]. The role for iron deficiency in the pathogenesis of uremic RLS is supported by Roger et al [31] who demonstrated an improvement in RLS symptoms following treatment with erythropoietin in a sub-group of adult ESRD patients with hemoglobin levels that were significantly lower than non-RLS patients.…”
Section: Discussionmentioning
confidence: 99%
“…RLS appears to be related to alterations in dopaminergic and opioid neuronal pathways within the central nervous system. This implies that iron deficiency plays a role in the etiology of RLS, since iron is a co-factor for dopamine production within nigrostriatal regions of the basal ganglia (i.e., substantia nigra, putamen, and caudate) and is a modulator of dopamine receptors [30]. The role for iron deficiency in the pathogenesis of uremic RLS is supported by Roger et al [31] who demonstrated an improvement in RLS symptoms following treatment with erythropoietin in a sub-group of adult ESRD patients with hemoglobin levels that were significantly lower than non-RLS patients.…”
Section: Discussionmentioning
confidence: 99%
“…37], Several hy potheses have been advanced to explain this distribution, particularly in terms of neurotransmitter metabolism. Youdim et al [38][39][40][41][42] have suggested that this distribution pat tern reflects the presence of the dopamine D2 receptor, which is claimed to contain iron. Evidence to support a role of iron in D2 receptor function is the reduction in D2 recep tor binding by metal ion chelators [38], and the alterations of dopaminergic activity found in iron-deficient rats [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Youdim et al [38][39][40][41][42] have suggested that this distribution pat tern reflects the presence of the dopamine D2 receptor, which is claimed to contain iron. Evidence to support a role of iron in D2 receptor function is the reduction in D2 recep tor binding by metal ion chelators [38], and the alterations of dopaminergic activity found in iron-deficient rats [39][40][41][42]. The present study, however, shows that the high est levels of iron are found, not in the caudate, putamen and substantia nigra zona compacta where D2 receptors appear to be located in greatest density [43], but in the glo bus pallidus, substantia nigra zona reticulata and red nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that iron is essential for the normal functioning of the dopamine D 2 receptor. 15 Hence, the reduction in serum iron levels that occurs in the acute phase response may result in a decreased number of functional dopamine D 2 receptors in the brain. In a setting of dopamine blockade induced by antipsychotic medication, this loss of receptors may trigger an acute reduction in dopaminergic transmission mediated by D 2 receptors and thereby give rise to the rigidity, staring and mutism that are characteristic of neuroleptic malignant syndrome.…”
Section: Can the Acute Phase Response Explain The Core Features Of Nementioning
confidence: 99%